2018
DOI: 10.1177/1729881418783119
|View full text |Cite
|
Sign up to set email alerts
|

An improved nonlocal sparse regularization-based image deblurring via novel similarity criteria

Abstract: Image deblurring is a challenging problem in image processing, which aims to reconstruct an original high-quality image from its blurred measurement caused by various factors, for example, imperfect focusing caused by the imaging system or different depths of scene appearing commonly in our daily photos. Recently, sparse representation whose basic idea is to code an image patch as a linear combination of a few atoms chosen out from an overcomplete dictionary has shown uplifting results in image deblurring. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Table 1 gives the PSNR and SSIM of existing and proposed deblurring method for various digital blur images of CERTH dataset. From table 1 it is observed that, the proposed method gives 16%,14%,11%,7%,5% and 2% high average PSNR compared to recently analyzed methods of Wenqi et al [29], Clemens et al [20], Wang et al [28], Hongyan et al [30], Minghua et al [2], and Dong et al [31] respectively due to high texture detail description and predictor correlation. image, it has been observed that the proposed deblurred image is clearer than the existing methods, as the elastic net is consistent in prediction and feature selection by removing staircase effect.…”
Section: Deblurring Evaluation Of Different Methods For Digital Blurmentioning
confidence: 82%
See 3 more Smart Citations
“…Table 1 gives the PSNR and SSIM of existing and proposed deblurring method for various digital blur images of CERTH dataset. From table 1 it is observed that, the proposed method gives 16%,14%,11%,7%,5% and 2% high average PSNR compared to recently analyzed methods of Wenqi et al [29], Clemens et al [20], Wang et al [28], Hongyan et al [30], Minghua et al [2], and Dong et al [31] respectively due to high texture detail description and predictor correlation. image, it has been observed that the proposed deblurred image is clearer than the existing methods, as the elastic net is consistent in prediction and feature selection by removing staircase effect.…”
Section: Deblurring Evaluation Of Different Methods For Digital Blurmentioning
confidence: 82%
“…A low rank prior to blind image deblurring is more complex in natural images and obtains low accuracy during evaluation [29]. Non local sparse regularization L0 [28] and L0-regularized intensity for gradient prior [2] gives a competitive performance than motion tracking [20] but it provides less identification of kernel and sparsity. Group sparsity [31] based local group clustering provide better results but distortion occurs around the edges.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SSIM has been repeatedly improved, with several derivative methods developed, such as gradient-based SSIM (GSSIM), three-component weighting region, four-component weighting region, complex wavelet, and an improved SSIM with a sharpness comparison (ISSIM-S) [ 31 , 32 , 33 , 34 , 35 ]. In these advanced implementations, SSIM was transformed to demonstrate reasonable performance in assessing images without a reference and can be used for image decomposition, identifying inter-patch and intra-patch similarities, and deblurring IQA [ 36 , 37 , 38 , 39 ]. SSIM is used widely to evaluate images, including medical images; therefore, this study presents four types of SSIM as a computer-based observer to assess DOT reconstructed images.…”
Section: Introductionmentioning
confidence: 99%